Effects of anger regulation and social anxiety on perceived stress. Issue 2 (27th August 2015) - Yamaguchi, Ayano; Kim, Min-Sun; Akutsu, Satoshi; Oshio, Atsushi
The mediating role of social anxiety was explored within the effect of anger regulation on perceived stress in the national sample of American and Japanese older adults. Results indicated that anger suppression is a significant factor in perceived stress mediated by social anxiety. Anger suppression was also directly related to perceived stress. The correlation of anger suppression with social anxiety was stronger in Japan than in the United States. Understanding both universal and culture-specific aspects of emotion regulation and perceived stress will be essential for the development of sound theory, future research, and effective prevention and intervention efforts.